Journal of Ecclesiatical History (Cambridge University Press)
The journal's scope extends to cultural, institutional, intellectual, political, social and any other relevant form of history; to all periods from ancient to modern; and to all regions of the world. Contributors address detailed research questions as well as engaging with the wider issues in the field.
Keywords: Religion